What can the structure of the palm print tell us? - Wei, Xiaoliang (2015)
Palm reading has been practised worldwide since ancient times. Traditionally, it is used as a tool of fortune telling and character indicator. Recent studies criminal identification in different regions. In addition, some recent researches show that diagnosis on certain diseases can be achieved by analysing the structure of the palm prints. However, few research is conducted to find out if palm print can be an accurate indicator of characteristics. This project aims to understand traditional palm reading techniques and verify whether palm prints reflect the characteristics of a person. Due to time constraint and limited data input, only one technique is selected to be verified in this project. It states that if a person’s hands have similar palm prints, he or she tends to speak bluffly. Therefore, a piece of software is built to calculate the similarity between left and right palm prints and compare the result with a palm print database. The database was built by collecting palm prints from friends and relatives using a digital camera. It contains palm prints of both genders across continents with different ages. Thus it has a good variety of palm prints to represent the whole population. Three experiments were conducted using palm prints of three persons who were believed to speak bluffly by their friends and relatives. The results shows that these two out of three persons have higher similarity of their palm prints when comparing against the results of the database. However, one of them has a lower similarity compared with the database. This implies that people with similar palm prints do speak straightforwardly and honestly to others while there might also be exceptions. As this project only assessed a small portion of the whole palm reading techniques, it is possible to carry out more experiments to verify other techniques for future works.